DESIGN RESEARCH ON RATIO AND PROPORTION LEARNING BY USING RATIO TABLE AND GRAPH WITH OKU TIMUR CONTEXT AT 7th GRADE - Haniful Muttaqin; Ratu Ilma Indra Putri; Somakim Somakim (Journal on Mathematics Education, 2017)
This research was motivated by several studies which show that students have difficulties in understanding the material ratio, wherein one contributing factor is the lack of ability in proportional reasoning. The purpose of this study is to produce a trajectory of learning to help students develop abilities in comparison reasoning. Solution strategies in this study were the ratio tables and graphs using PMRI approach (Indonesian Realistic Mathematics Education) with OKU Timur context. This research was conducted in MTs Subulussalam 2 Sriwangi Ulu OKU Timur. The method used was design research with three stages, those are the preliminary experiment, design experiment, and retrospective analysis. At the preliminary experiment, researchers designed the Hypothetical Learning Trajectory (HLT). At the design experiment, HLT tested on students to develop informal knowledge into a formal knowledge of mathematics through activities. The trial results were analyzed in a retrospective analysis phase so that the trajectory of learning or Learning Trajectory (LT) resulted.DOI:Â http://dx.doi.org/10.22342/jme.8.2.3969.211-222